Klotho inversely relates with carotid intima- media thickness in atherosclerotic patients with normal renal function (eGFR ≥60 mL/min/1.73m2): a proof-of-concept study - Donate-Correa, Javier; Martín-Núñez, Ernesto; Martin-Olivera, Alberto; Mora-Fernández, Carmen; Tagua, Víctor G.; Ferri, Carla M.; López-Castillo, Ángel; Delgado-Molinos, Alejandro; López-Tarruella, Victoria Castro; Arévalo-Gómez, Miguel A.; Pérez-Delgado, Nayra; González-Luis, Ainhoa; et al. (Frontiers in Endocrinology, 2023)
Klotho protein is predominantly expressed in the kidneys and, at lesser extent, in vascular tissue, and peripheral blood circulating cells. Carotid artery intima-media thickness (CIMT) burden, a marker of subclinical atherosclerosis, has been related with reductions in circulating Klotho levels in chronic kidney disease patients, who show reduced Klotho levels in all stages of the disease. However, the contribution of serum Klotho and its expression levels in peripheral blood circulating cells and in the carotid artery wall on the CIMT in the absence of kidney impairment has not been assessed yet. In this work, we conducted a single-center study in 35 atherosclerotic patients with preserved kidney function subjected to elective carotid surgery. Patients with higher values of CIMT showed reduced Klotho levels in serum (430.8 [357.7-592.9] vs. 667.8 [632.5-712.9] pg/mL; p<0.001), mRNA expression in blood circulating cells and carotid artery wall (2.92 [2.06-4.8] vs. 3.69 [2.42-7.13], p=0.015; 0.41 [0.16-0.59] vs. 0.79 [0.37-1.4], p=0.013, respectively) and immunoreactivity in the carotids (4.23 [4.15-4.27] vs. 4.49 [4.28-4.63] µm2, p=0.008). CIMT was inversely related with Klotho levels in serum (r= -0.717, p<0.001), blood mRNA expression (r=-0.426, p=0.011), and with carotid artery mRNA and immunoreactivity levels (r= -0.45, p=0.07; r= -0.455, p= 0.006, respectively). Multivariate analysis showed that serum Klotho, together with the expression levels of tumor necrosis factor TNFα in blood circulating cells, were independent determinants of CIMT values (adjusted R2=0.593, p<0.001).